Crafting Linear Motion Problems for ProblemBased Learning Physics Classes - Hajar Ramzan, Siti; Farahwahidah Abdul Rahman, Nor; Suhailah Mohd, Nor (International Journal of Psychosocial Rehabilitation, 2020)
Problem-based learning (PBL) is an inquiry-based learning where students begin with an ill-structured problem and regulate themselves for knowledge construction. Unlike the traditional approach, PBL attention is directed to students’ agency as knowledge constructors, where it provides authentic experiences that promote active learning (to work cooperatively in a group), support knowledge construction (gather information across disciplines/subjects), and naturally integrate school learning with real life (to seek solutions to real-world problems). SMK SETA is one of the pioneer schools for implementing problem-based learning (PBL) under the STEM education initiative using low carbon as a theme. Crafting an ill-structured problem of low-carbon theme becomes a critical skill for the teachers where there is no formula for developing an effective problem. Teachers identify learning issues related to the low-carbon theme, align them with the curriculum, and comply with a lesson plan by the principle of constructive alignment to adapt in PBL classes. Students of PBL are more likely to be active, creative, and enthusiastic and work independently, while the teacher’s role is only as a facilitator. In line with the Malaysia Education Blueprint, PBL promotes 21st-century learning and higher-order thinking skills (HOTS) and improves the quality of STEM education in Malaysia. Therefore, assigning an ill-structured problem during a physics lesson invites students’ engagement in a real-life experience because it helps to enhance students’ critical thinking skills and problem-solving skills and promotes lifelong learning. Implementing PBL into lessons, however, is challenging, particularly at the stage of problem crafting. The challenge to construct an ill-structured problem becomes a huge obstacle for teachers to adopt PBL as their teaching strategy. This paper describes the process of how an ill-structured problem can be constructed for PBL physics classes. The problem has to trigger the interest of students and relate to the physics curriculum learning outcomes. This paper will discuss the strategic ways that can be employed in developing an ill-structured problem. The discussion is directed to the issues, challenges, and ways to overcome the challenges when crafting the ill-structured problem for the secondary level.